2015
DOI: 10.1038/ncomms9202
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-selective mechanisms of arrestin conformations and functions revealed by unnatural amino acid incorporation and 19F-NMR

Abstract: Specific arrestin conformations are coupled to distinct downstream effectors, which underlie the functions of many G-protein-coupled receptors (GPCRs). Here, using unnatural amino acid incorporation and fluorine-19 nuclear magnetic resonance (19F-NMR) spectroscopy, we demonstrate that distinct receptor phospho-barcodes are translated to specific β-arrestin-1 conformations and direct selective signalling. With its phosphate-binding concave surface, β-arrestin-1 ‘reads' the message in the receptor phospho-C-tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
180
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(188 citation statements)
references
References 63 publications
5
180
0
1
Order By: Relevance
“…PKC-phosphorylation was sufficient to induce conformational changes in β-arrestin2 N-domain. This role of K11,12 is in good agreement with the results of a previous study, where phosphopeptide-induced β-arrestin1 conformational shifts were investigated (55). Interestingly, the C-domain sensors (F225, F263) in arrestin did not respond to the recruitment upon PKC-phosphorylation of the receptor or in the absence of stability lock, indicating that both stability lock and receptor activity are required for the full set of structural rearrangements in the Cdomain.…”
Section: O N F I D E N T I a L Heterologous Regulation Of Inactive supporting
confidence: 78%
See 1 more Smart Citation
“…PKC-phosphorylation was sufficient to induce conformational changes in β-arrestin2 N-domain. This role of K11,12 is in good agreement with the results of a previous study, where phosphopeptide-induced β-arrestin1 conformational shifts were investigated (55). Interestingly, the C-domain sensors (F225, F263) in arrestin did not respond to the recruitment upon PKC-phosphorylation of the receptor or in the absence of stability lock, indicating that both stability lock and receptor activity are required for the full set of structural rearrangements in the Cdomain.…”
Section: O N F I D E N T I a L Heterologous Regulation Of Inactive supporting
confidence: 78%
“…the canonical homologous and the novel heterologous activation, induce β-arrestin binding to the same receptor in different conformations in a physiologically relevant setting. Previous studies suggested that the multiple active conformations of β-arrestins have different functions (55,57,58). This may explain our finding that the PKC-induced β-arrestin2 recruitment directed the receptor to Rab7-enriched late endosomes to a lesser extent than AngII.…”
Section: O N F I D E N T I a L Heterologous Regulation Of Inactive supporting
confidence: 66%
“…The scaffolding function of βarrs, as signal transducers, has been characterized for multiple signaling proteins, including c-Src (18,19). Formation of GPCR-βarr1-c-Src ternary complexes has been demonstrated to regulate multiple cellular functions downstream of various GPCRs (20).…”
Section: Resultsmentioning
confidence: 99%
“…For example, ␤arr1 can bind between blades 1 and 2 of the clathrin ␤-propeller via an intrinsically disordered clathrin-binding box, but can also interact with a binding pocket formed by blades 4 and 5 of clathrin via an 8-amino acid splice loop found only in the long ␤arr1 isoform (99). Further insights into the allosteric regulation of ␤arr signaling have recently been provided by an NMR study that used 19 F probes in ␤arr1 to probe changes in its structure induced by different phosphopeptides derived from the V2R C terminus (100). Although all the phosphopeptides interacted with the phosphate sensor to induce changes in the finger and middle loops, there were also distinct phospho-interaction patterns that were related to the spacing of the multiple ␤arr phospho-binding sites.…”
Section: Signal Transduction To Effectorsmentioning
confidence: 99%